Three-dimensional printed model as a valuable tool in partial nephrectomy for a high complexity renal tumor. Issue 4 (October 2017) - Saeedi, Yaser; Kotiesh, Kais
Aim: Case presentation of a 43-year-old female prepared for partial nephrectomy with contrast-enhanced CT scan, R.E.N.A.L nephrometery score and 3D printed model.Method:  3D printed kidney model using 3D printing technology, stereolithography was  used in partial nephrectomy for a high complexity renal mass.Result: Partial nephrectomy without complications for clear cell renal cell carcinoma with focal microcystic changes – G2; pT1a with negative surgical margins.Summary: 3D printed model of the kidney in a high complexity case for partial nephrectomy was a vital tool for preoperative planning and of a great intraoperative value to localize and remove the tumor, making a high-risk procedure uneventful and smooth. Further study is required to evaluate the value of 3D printed models in medium- and high-risk groups of patients.